2015
DOI: 10.1007/s40258-015-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Studies Evaluating the Cost Utility of Screening High-Risk Populations for Latent Tuberculosis Infection

Abstract: With validity issues in terms of parameters and assumptions, any conclusion should be interpreted with caution. Despite this, some cautionary recommendations emerged: screening HIV patients with a TST is highly cost effective, while screening adult immigrants with an IGRA is moderately cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Hill et al modelled the effect of different TB control interventions on TB incidence in the USA projecting over the next 50 years and concluded that "targeted testing and treatment of LTBI will be necessary (…) to achieve levels close to elimination in an acceptable timeframe" (66) (75). The key finding of the cost-effectiveness of TSTbased migrant screening has been corroborated elsewhere (76). This has to be balanced against potential overdiagnosis/overtreatment (due to the reduced specificity) and feasibility in programmatic screening and the practicalities including the need to return for reading.…”
Section: Impact On Host Country Epidemiologymentioning
confidence: 98%
“…Hill et al modelled the effect of different TB control interventions on TB incidence in the USA projecting over the next 50 years and concluded that "targeted testing and treatment of LTBI will be necessary (…) to achieve levels close to elimination in an acceptable timeframe" (66) (75). The key finding of the cost-effectiveness of TSTbased migrant screening has been corroborated elsewhere (76). This has to be balanced against potential overdiagnosis/overtreatment (due to the reduced specificity) and feasibility in programmatic screening and the practicalities including the need to return for reading.…”
Section: Impact On Host Country Epidemiologymentioning
confidence: 98%
“…For instance, although TB systematic screening has been studied in aspects of methodology, algorithms and in different high-risk populations, the direct evidence remains weak for the impact of screening on health outcomes and TB transmission when compared with passive case-finding alone [51, 52, 69]. Some new diagnostic tools, like Xpert MTB/RIF, have been evaluated recently in many high-risk groups other than in the elderly [69–71]. The evaluation of cost-effectiveness, feasibility and acceptability under specific circumstances also lacks independent study design in the elderly.…”
Section: Research Gapsmentioning
confidence: 99%
“…Previous economic analyses have been performed to assess the cost-effectiveness of mass post-landing screening of new migrants to low-incidence countries, several of which have been highlighted in systematic reviews [ 58 60 ]. In an analysis by Dasgupta et al [ 11 ], post-landing surveillance was evaluated for its ability to prevent TB cases in new immigrants to Montreal.…”
Section: Discussionmentioning
confidence: 99%